Smart traffic light / Muhammad Ikhmal Haziq Saiful Nizam & Mohamad Akhmal Rosli - Saiful Nizam, Muhammad Ikhmal Haziq; Rosli, Mohamad Akhmal (2015)
In Malaysia, traffic light are typically controlled by a Programmable Logic Controller. The typical traffic light does contribute to time wastage where some stays RED (stop) even though there are no users on the other junction. Therefore, our project will be focusing on the four junction traffic light for night application. During day time, the traffic light will be function as usual. Whereas, at night the traffic light will stays GREEN only on the main road but stays RED on the other junction. If there is a car from the other junction, it will trigger the LDR sensor to switch the light from RED to GREEN. The traffic light will stays GREEN for a while. Then, the traffic light on the junction will switch back to RED and the traffic light on the main road will switch to GREEN and stays. It will be the same for the other junction. Moreover, during night time the LDR sensor for the street light also will be triggered that will tum ON all of them. In addition, our project will use solar power as a backup if there is any possibility to a power failure.